دراسة تحليلية لأهداف التربية الرياضية بالمعاهد الأزهرية في ضوء فلسفة ومناهج التعليم بالأزهر الشريف - حسن، أحمد ماهر حسن أنور; معارك، أحمد عبدالعزيز محمد محمد; محمد، حاتم عوض Mohammed, Hatem Awad (جامعة حلوان - كلية التربية الرياضية للبنين, 2021)
And because the school curriculum is a tool through which the goals of the school are achieved in the movement of preserving heritage and the movement of social change, where the community faces many problems, whether at the level of construction or implementation, and the curriculum must address these problems, and because the school deals with human beings, each of whom has his own emotions and feelings, and that human relations within The school has an impact on friction between students. Since the researcher’s goal is to carry out an analytical study of the objectives of physical education in Al-Azhar institutes in the light of the philosophy and curricula of education in Al-Azhar Al-Sharif. Al-Azharah in seven governorates of the Arab Republic of Egypt The results showed that there are indicators characterized by the degree of achievement of the goals of physical education in Al-Azhar institutes according to the opinions of a sample, which is that the goals achieve the recreational aspect, and the student develops loyalty and belonging to the homeland. The content is in a logical order, and the content is diverse The results also showed that there are some shortcomings in the degree to which they achieve the objectives of physical education in Al-Azhar institutes according to the opinions of the research sample, and it does not help to build the integrated personality, and does not care about the cognitive development of the student. The content is not linked to the objectives of the curriculum, is not commensurate with the students' abilities, and the content does not seek to achieve the objectives of Al-Azhar in general. The researcher recommended working on the formulation of a unified intellectual framework for the goals of physical education in Al-Azhar institutes in the light of a clear educational philosophical basis and in keeping with the various changes taking place in society, and the formation of specialized and qualified committees composed of educational experts working to formulate the goals of school sports in the light of a clear and consistent educational philosophical basis. Various changes taking place in society."
ولكون المنهج المدرسي أداة تتحقق بواسطتها أهداف المدرسة في حركة المحافظة على التراث وحركة التغير الاجتماعي، حيث يواجه المجتمع كثيرا من المشكلات سواء على مستوى البناء أو التنفيذ ولا بد للمنهج من معالجة هذه المشاكل ولكون المدرسة تتعامل مع بشر لكل منهم عواطفه ومشاعره الخاصة وأن العلاقات الإنسانية داخل المدرسة أثر في حدوث احتكاك بين الطلبة. وحيث إن هدف الباحث القيام بدراسة تحليلية لأهداف التربية الرياضية بالمعاهد الأزهرية في ضوء فلسفة ومناهج التعليم بالأزهر الشريف، وقد استخدم الباحث المنهج الوصفي، حيث قام الباحث بعمل استبيان مكون من محورين، وكان عدد عينه البحث (151) معلم وموجه من معلمي وموجهي التربية الرياضية بالمعاهد الأزهرية بعدد سبع محافظات من جمهورية مصر العربية وأظهرت النتائج أن هناك مؤشرات تميزت بدرجة تحقيقها لأهداف التربية الرياضية بالمعاهد الأزهرية وفقا لأراء عينة وهي أن الأهداف تحقق الجانب الترويحي، وينمى لدى التلميذ الولاء والانتماء للوطن، ويستمد منهج التربية الرياضية أهدافه من السياسة التعليمية العامة للأزهر الشريف، ويحتوى على أنشطة فردية وأنشطة جماعية، ويتسم المحتوى بالترتيب المنطقي، ويتسم المحتوى بالتنوع كما أظهرت أيضا النتائج أن هناك بعض القصور في بدرجة تحقيقها لأهداف التربية الرياضية بالمعاهد الأزهرية وفقا لأراء عينة البحث وهي لا يساعد على بناء الشخصية المتكاملة، ولا يهتم بتنمية التلميذ معرفيا. ولا يرتبط المحتوى بأهداف المنهج، ولا يتناسب مع قدرات التلاميذ، ولا يسعى المحتوى إلى تحقيق أهداف الأزهر بشكل عام، وقد أوصى الباحث العمل على صياغة أطار فكري موحد لأهداف التربية الرياضية بالمعاهد الأزهرية في ضوء أساس فلسفي تربوي واضح وتساير مختلف التغيرات الحادثة في المجتمع، وتشكيل لجان متخصصة ومؤهله مكونة من خبراء تربويين تعمل على صياغة أهداف الرياضة المدرسية في ضوء أساس فلسفي تربوي واضح وتساير مختلف التغيرات الحادثة في المجتمع. "
Keywords: التربية الرياضية -- المعاهد الأزهرية -- المناهج الدراسية -- التعليم الأزهري